Segmental involvement of the corpus callosum in C9orf72-associated ALS: a tract of interest-based DTI study. (March 2021) - Müller, Hans-Peter; Lulé, Dorothée; Roselli, Francesco; Behler, Anna; Ludolph, Albert C.; Kassubek, Jan
Background: C9orf72 hexanucleotide repeat expansions are associated with widespread cerebral alterations, including white matter alterations. However, there is lack of information on changes in commissure fibres. Diffusion tensor imaging (DTI) can identify amyotrophic lateral sclerosis (ALS)-associated patterns of regional brain alterations at the group level. The objective of this study was to investigate the structural connectivity of the corpus callosum (CC) in ALS patients with C9orf72 expansions. Methods: DTI-based white matter mapping was performed by a hypothesis-guided tractwise analysis of fractional anisotropy (FA) maps for 25 ALS patients with C9orf72 expansion versus 25 matched healthy controls. Furthermore, a comparison with a patient control group of 25 sporadic ALS patients was performed. DTI-based tracts that originate from callosal sub-areas I to V were identified and correlated with clinical data. Results: The analysis of white matter integrity demonstrated regional FA reductions for tracts of the callosal areas II and III for ALS patients with C9orf72 expansions while FA reductions in sporadic ALS patients were observed only for tracts of the callosal area III; these reductions were correlated with clinical parameters. Conclusion: The tract-of-interest-based analysis showed a microstructural callosal involvement pattern in C9orf72- associated ALS that included the motor segment III together with frontal callosal connections, as an imaging signature of the C9orf72 -associated overlap of motor neuron disease and frontotemporal pathology.